Web based online diagnosis for erectile dysfunction using International Index of Erectile Function (IIEF) - Ibrahim, M.N.M.; Ibrahim, F.; Razack, A.H. (2008)
Most Erectile Dysfunction (ED patients are not willing to openly discuss their problems with friends and physicians. Because of this issue, this paper proposes a web based online diagnosis of Erectile Dysfunction using International Index of Erectile Function (IIEF) questionnaire which will give an opportunity for ED patients to asses themselves at their private surroundings and convenient time. This system allows patients to logon to the web sites to answer questionnaire. Patient's responses can be used to calculate the IIEF score. Advice to consult physician will be given if the IIEF score is below 21. Moreover, online consultations and diagnosis can save valuable time and travelling cost for patients and physicians. The web based application was built on .Net Framework and Active Server Pages .NET (ASP.NET). Internet Information Server (IIS) as web server, while Microsoft SQL 2008 Express Edition is used as main database Â© 2008 Springer-Verlag.